A polylactic acid nucleating agent with plasticizing function and its preparation method and application

By using polylactic acid nucleating agents prepared by tomato peel powder and coupling agent, the problems of poor thermal processing performance and high cost of polylactic acid in the prior art are solved, and the effects of high crystallization rate, good thermal processing performance and biodegradability are achieved.

CN118978813BActive Publication Date: 2025-04-25BEIFANG UNIV OF NATITIES +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411066049.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-05
Publication Date
2025-04-25
Estimated Expiration
2044-08-05

AI Technical Summary

Technical Problem

While the existing polylactic acid nucleating agents are unable to effectively improve their thermal processing performance while increasing the crystallization rate of polylactic acid, they also have problems of biocompatibility and high cost.

Method used

Tomato peel powder is used as the nucleating agent, and a coupling agent is added thereto, and melt blending is performed through a high-speed mixer to prepare a polylactic acid nucleating agent with plasticization function.

Benefits of technology

It significantly improves the crystallization rate, impact performance and thermal processing rheology of polylactic acid, while maintaining its biodegradability, reducing raw material costs, and achieving effective waste utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118978813B_ABST
    Figure CN118978813B_ABST
Patent Text Reader

Abstract

The present invention discloses a polylactic acid nucleating agent with a plasticizing function, a preparation method and an application thereof, wherein the nucleating agent comprises tomato peel residue. Since the nucleating agent of the present invention comprises tomato peel residue powder having a lamellar structure, it not only improves the crystallization performance, impact performance and thermal processing rheology of polylactic acid, but also maintains the characteristic of complete biodegradability after being compounded with polylactic acid. The tomato peel residue powder is derived from naturally sun-dried tomato peel residue. The waste tomato peel residue is dried and crushed into a powder with a certain particle size as the raw material of the nucleating agent. The powder has the characteristics of abundant raw material sources, low cost, easy processing and biodegradability, and solves the problem of accumulation of a large amount of tomato peel waste generated in tomato processing and production, realizes waste utilization, and achieves the purpose of green environmental protection, energy saving and emission reduction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of preparation of composite polylactic acid, in particular to a polylactic acid nucleating agent with plasticizing function and a preparation method and application thereof. Background Art

[0002] Polylactic acid (PLLA), as a biodegradable polymer material with high compatibility with materials and environmental friendliness, has been widely used in biomedicine, degradable packaging, 3D printing and other fields. However, the shortcomings of PLLA, such as slow crystallization rate, high brittleness and poor thermal processing stability, limit its further application scope.

[0003] In order to increase the use of PLLA, it is necessary to increase the crystallization rate of PLLA. Different strategies have been used to improve the crystallization kinetics of PLLA. One method is to introduce a crystallization nucleating agent so that crystallization occurs at a higher temperature or a faster cooling rate. Nucleating agents can reduce the free energy barrier for crystallization nucleation. Another way to improve the crystallization kinetics of PLLA is to increase the mobility of the polymer chain by adding a plasticizer, which can reduce the energy required for the molecular chain to fold.

[0004] Nucleating agents are widely used to adjust the crystallization behavior of semi-crystalline polymers, including accelerating crystallization kinetics, increasing crystallinity, reducing grain size, inducing specific crystal structures and morphologies, etc., which have a huge impact on the final performance of polymer products. Under actual processing conditions, such as traditional injection molding and extrusion molding with a large cooling rate, poor performance such as poor mechanical, barrier properties and heat resistance is caused. Adding nucleating agents is considered to be one of the most useful and simplest methods to obtain highly crystalline products from semi-crystalline polymers with slow crystallization kinetics. At present, the nucleating agents of polylactic acid mainly include inorganic nucleating agents (such as talc, clay, etc.), organic nucleating agents (such as sorbitol, stearamide) and polymer nucleating agents. These nucleating agents can increase the crystallization rate of PLLA. However, the lack of compatibility and non-degradability of inorganic nucleating agents with PLLA, as well as the high cost and non-degradability of organic nucleating agents, all affect the biocompatibility, complete degradability and raw material cost of the materials obtained after being composited with PLLA; according to the above standards, the interface interaction and / or lattice matching between many reported nucleating agents and polymer matrices is not favorable enough, which may be the main reason for the limited nucleation and crystallization customization effect. In addition, there is no related patent or literature on existing PLLA nucleating agents that can improve the thermal processing properties of PLLA. Therefore, the development of low-cost biodegradable biomass nucleating agents has become the key to preparing fully degradable PLLA composite materials with fast crystallization rate, excellent toughness and good thermal processing properties. Summary of the invention

[0005] The purpose of the present invention is to provide a polylactic acid nucleating agent with plasticizing function and its preparation method and application. The nucleating agent has good miscibility with polymers and has nucleating, plasticizing and toughening properties.

[0006] In order to solve the problems existing in the prior art, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a polylactic acid nucleating agent with plasticizing function, comprising tomato peel residue.

[0008] Furthermore, the nucleating agent also includes a coupling agent.

[0009] Furthermore, the mass ratio of the tomato peel residue to the coupling agent is 3-9:0-6, preferably 3-8:1.

[0010] Furthermore, the coupling agent is selected from silane coupling agents, preferably KH550, KH560 or KH570.

[0011] Preferably, the tomato peel residue is dried tomato peel residue powder.

[0012] Furthermore, the average particle size of the tomato peel residue powder is in the range of 1 to 70 microns, preferably 3 to 10 microns.

[0013] In a second aspect, the present invention provides a method for preparing the polylactic acid nucleating agent described in the first aspect, comprising the following steps:

[0014] ① Put the dried tomato peel residue into a high-speed grinder for grinding to obtain coarse tomato peel residue powder;

[0015] ② In order to ensure the uniformity of the powder, use a 20-mesh standard sieve to screen the coarse powder;

[0016] ③Put the screened coarse powder in a planetary ball mill and perform ball milling at a speed of 600 rpm for 4 to 6 hours to obtain tomato peel residue powder. This process significantly reduces the particle size of the powder, and finally tomato peel residue powder with an average particle size of 4 to 5 microns can be prepared.

[0017] In a third aspect, the present invention provides a polylactic acid composite material, comprising: polylactic acid and the polylactic acid nucleating agent described in the first aspect, wherein the mass of the polylactic acid nucleating agent is (1 to 20)%, preferably (3 to 5)% of the mass of the polylactic acid.

[0018] In a fourth aspect, the present invention provides a method for preparing the polylactic acid composite material according to the third aspect, comprising the following steps:

[0019] ① Place the polylactic acid in an oven and dry it at 80℃ to 90℃ for 6 to 8 hours to remove moisture; this step can ensure the stability and reactivity of the polylactic acid particles in subsequent experiments, and is essential for maintaining the physical and chemical properties of the polylactic acid particles.

[0020] ② The nucleating agent described in the first aspect above is melt-blended with polylactic acid in a high-speed mixer to mix the materials evenly.

[0021] Further, the melt blending of the nucleating agent and polylactic acid comprises the following steps:

[0022] The nucleating agent and polylactic acid are uniformly mixed, and the mixture is placed in a torque rheometer at 160-170°C and a rotation speed of 40-50 rpm for melt blending for 6-8 minutes, or the mixture is extruded and granulated through a parallel twin-screw, with the temperature of the screw heating zone being 150-200°C and the screw speed being 200 rpm. Through this melt blending step, not only the effective mixing of the two materials is ensured, but also the homogeneity of the composite material is ensured.

[0023] The advantages and beneficial effects of the present invention are:

[0024] The polylactic acid nucleating agent with plasticizing function of the present invention includes tomato peel residue powder with lamellar structure characteristics, which not only improves the crystallization performance, impact performance and thermal processing rheology of polylactic acid, but also maintains the characteristic of complete biodegradability after compounding with polylactic acid. The tomato peel residue powder comes from naturally sun-dried tomato peel residue. The waste tomato peel residue is dried and crushed into a powder with a certain particle size as the raw material of the nucleating agent. It has the characteristics of abundant raw material source, low cost, easy processing and biodegradability, and solves the problem of accumulation of a large amount of tomato peel waste generated in tomato processing and production, realizes waste utilization, and achieves the purpose of green environmental protection, energy saving and emission reduction.

[0025] The invention is prepared by adding a coupling agent to tomato peel residue powder and mixing the mixture with a high-speed mixer. The addition of the coupling agent further improves the crystallization performance of polylactic acid (PLLA), thereby reducing the cost of polylactic acid and improving its crystallization performance and fluidity. The polylactic acid has good biodegradability and low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The microscopic morphology of the prepared tomato peel residue powder;

[0027] In the figure: e is the microscopic morphology of tomato peel residue powder after ball milling for 2 h at a speed of 600 rpm;

[0028] f is the microscopic morphology of tomato peel residue powder after ball milling for 3 h at a speed of 600 rpm;

[0029] g is the microscopic morphology of tomato peel residue powder after ball milling for 4 h at a speed of 600 rpm;

[0030] h is the microscopic morphology of tomato peel residue powder after ball milling for 5 h at a rotation speed of 600 rpm;

[0031] Figure 2 DSC curve of non-isothermal crystallization of TP / PLLA composites;

[0032] Figure 3 is the effect of TP content on the shear viscosity of PLLA;

[0033] Figure 4 The effect of TP content on the melt index of PLLA;

[0034] Figure 5 The effect of TP content on the mechanical properties of PLLA;

[0035] Figure 6 isothermal crystallization curves of PLLA and TP / PLLA, where:

[0036] a is the isothermal crystallization curve of PLLA;

[0037] b is the isothermal crystallization curve when the tomato peel powder content is 1%;

[0038] c is the isothermal crystallization curve when the tomato peel powder content is 3%;

[0039] d is the isothermal crystallization curve when the tomato peel powder content is 5%;

[0040] e is the isothermal crystallization curve when the tomato peel powder content is 10%;

[0041] f is the isothermal crystallization curve when the tomato peel powder content is 15%. DETAILED DESCRIPTION

[0042] The following will be combined with the drawings in the embodiments of the present application to clearly describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments in the present application belong to the scope of protection of this application.

[0043] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0044] Polylactic acid was purchased from Natureworks 4032D in the United States.

[0045] Experimental Example 1

[0046] The purpose of this experiment was to investigate the effect of tomato peel pomace (TP) as a natural filler on the properties of polylactic acid (PLLA) matrix, and how to optimize the properties of TP / PLLA composites by adjusting the tomato peel content.

[0047] 1. Preparation of composite materials:

[0048] In this experiment, the method of preparing TP / PLLA composites by mixing tomato pomace powder with polylactic acid at different mass fractions was explored. During the experiment, the prepared tomato pomace powder with an average particle size of 3 to 10 microns was first mixed with polylactic acid particles at a mass fraction of 0%, 1%, 3%, 5%, 10% and 15%. Subsequently, these mixtures were placed in a torque rheometer and melt blended at a temperature of 160°C and a speed of 40 rpm for 6 minutes to obtain six TP / PLLA composites.

[0049] 2. Experimental methods:

[0050] 2.1 Non-isothermal crystallization

[0051] In order to study the non-isothermal crystallization behavior of TP / PLLA composites, a detailed temperature program was designed in this experiment. First, the TP / PLLA composite sample was heated from room temperature to 200°C at a rate of 20°C / min and kept at this temperature for 2 minutes to ensure complete melting. Subsequently, the sample was rapidly cooled to room temperature at two different cooling rates (5°C / min and 40°C / min). This step was intended to observe the effect of different cooling rates on the crystallization behavior. Finally, the sample was heated to 200°C again at a rate of 20°C / min to evaluate its thermal stability and remelting behavior after crystallization. This process provides important experimental data for a deep understanding of the crystallization kinetics of the material.

[0052] 2.2 Isothermal crystallization

[0053] In the isothermal crystallization test, the sample was first heated from room temperature to 200°C at a rate of 10°C / min. This step was designed to quickly heat the sample to a relatively high temperature to facilitate the subsequent crystallization process.

[0054] The sample was then kept at 200°C for 2 minutes to ensure that the sample reached a thermodynamic equilibrium state. This step is critical to eliminate thermal stress inside the sample and achieve uniform temperature distribution.

[0055] Next, the samples were cooled at a rate of 10°C / min to specific isothermal crystallization temperatures, which were 96°C, 98°C, 100°C, 102°C, and 104°C. These temperature points were selected based on the melting point and crystallization characteristics of the materials in order to systematically study the effects of different temperatures on the crystallization behavior.

[0056] After reaching the isothermal crystallization temperature, the sample will be kept at this temperature for a period of time to observe and record the crystallization process. This step is important for evaluating the crystallization rate and crystallinity of the material at a specific temperature.

[0057] Through this isothermal crystallization test, we can study the crystallization kinetics of materials at different temperatures in detail, providing important data support for optimizing the processing technology and performance of materials. At the same time, this test method also provides an effective experimental means for comparing the crystallization properties of different materials.

[0058] 2.3 Mechanical testing

[0059] To evaluate the impact resistance of the material, this study followed the guidelines of the national standard GB / T1843-2008. Under this standard, the specimens were tested using an Izod impact testing machine. Specifically, five valid specimens were selected from each sample group for testing, and the average impact strength of these specimens was calculated to represent the overall impact resistance of the material. At the same time, in order to fully understand the mechanical properties of the material, a tensile property test was also performed. This test was conducted in accordance with the national standard GB / T1040.1-2018, in which an electronic universal testing machine was used to determine the tensile properties of the specimens. During the test, a constant tensile speed of 5mm / min was set, and the strength of the specimen was recorded when it broke. Similarly, five valid specimens were selected from each sample group for testing, and their average tensile strength was calculated to reflect the tensile properties of the material.

[0060] 3 Experimental results

[0061] 3.1TP improves the crystallization rate of PLLA

[0062] like Figure 2 As shown in the figure, the experimental results show that the addition of tomato pomace powder can significantly accelerate the crystallization rate of polylactic acid. When the tomato pomace powder content is less than 3%, its heterogeneous nucleation effect is not significant; however, when the tomato pomace powder content exceeds 5%, the heterogeneous nucleation effect becomes obvious, thereby promoting the crystallization process of polylactic acid. It is worth noting that the glass transition temperature (T g ) did not change significantly with the increase of tomato peel content.

[0063] like Figure 6As shown in the figure, further isothermal crystallization tests show that with the increase of tomato peel powder content, the isothermal crystallization rate of TP / PLLA composite material is improved, but its crystal structure does not change. Under the isothermal crystallization conditions of 96℃, when the tomato peel powder content is 15%, the half crystallization time (t 1 / 2 ) is 1.36min, which is similar to the half crystallization time of pure polylactic acid (t 1 / 2 Compared with the TP content (9.06 min), the crystallization rate increased by about 85%. In addition, the equilibrium melting point of the TP / PLLA composite material first increased and then decreased with the increase of TP content, but the melting temperature (T m ) remain basically unchanged.

[0064] The observation results of crystal growth showed that the growth of crystals of both polylactic acid and its composite materials was mainly carried out in a mixed growth mode of two-dimensional disk and three-dimensional sphere. This discovery is of great significance for understanding the microstructure and macroscopic properties of TP / PLLA composites.

[0065] In summary, the addition of tomato peel powder can effectively increase the crystallization rate of polylactic acid without significantly changing its crystal structure. By precisely controlling the content of tomato peel powder, the crystallization behavior and thermal properties of TP / PLLA composites can be adjusted, providing an effective way to develop bio-based materials with specific performance requirements. These findings provide an important scientific basis for understanding the crystallization behavior of TP / PLLA composites and provide theoretical support for their material design and performance optimization in practical applications.

[0066] 3.2 Tomato peel residue improves the flow processing properties of polylactic acid

[0067] Figure 3 , 4 The rheological properties of polylactic acid and its composite with tomato pomace are shown. Figure 3 As shown in the figure, with the increase of angular frequency, both materials show shear thinning phenomenon, that is, the viscosity decreases with the increase of shear rate. With the increase of tomato peel content, the range of Newtonian platform area expands, which indicates that the material can still maintain constant viscosity at higher shear rate. Figure 4 As shown in the figure, the viscosity of the melt shows an overall downward trend. When the tomato peel content exceeds 3%, the addition of tomato peel seems to reduce the interaction between the polylactic acid molecular chains, causing the viscosity of the composite to decrease rapidly with the increase of tomato peel content. When the tomato peel content reaches more than 3%, it can effectively reduce the melt viscosity of the TP / PLLA composite, thereby helping to improve the processing performance of the composite. This discovery is of great significance for optimizing the processing technology of composite materials and expanding their application areas.

[0068] 3.3 Tomato peel residue improves the toughening property of polylactic acid

[0069] like Figure 5 As shown in Figure 2, this study explored the effect of tomato pomace content on the mechanical properties of polylactic acid-based composites. With the increase of tomato pomace content, the tensile strength of TP / PLLA composites gradually decreased from 67.1MPa at 1% tomato pomace content to 36.3MPa at 15% tomato pomace content, which was 7.06% and 49.72% lower than that of pure polylactic acid, while the impact strength of TP / PLLA composites first increased and then decreased with the increase of tomato pomace content. When the tomato pomace content was 5%, the impact strength reached a peak value, which was 59.8% higher than that of pure polylactic acid. Under rapid cooling conditions, the cross section of pure polylactic acid was smoother, while the composites with 1% to 3% tomato pomace added showed a regular river-like impact cross section, showing the pull-out of the layered matrix and large-scale yielding. This shows that during the impact process, stress is transferred from the matrix to the interface, and silver streaks are generated at the interface to consume energy, thereby improving the impact strength of the material. When the tomato peel content increased to 15%, clustered structures and cracks appeared on the cross section, indicating uneven distribution and agglomeration of tomato peel, which led to stress concentration and material defects, reducing the impact strength.

[0070] Example 1

[0071] This embodiment provides a polylactic acid nucleating agent with a plasticizing function, which is composed of dried tomato peel residue powder with an average particle size of 3 to 10 microns.

[0072] The preparation method of the polylactic acid nucleating agent of this embodiment comprises the following steps:

[0073] ① Put the dried tomato peel residue into a high-speed grinder for grinding to obtain coarse tomato peel residue powder;

[0074] ② Use a 20-mesh standard sieve to screen the coarse powder.

[0075] ③ The screened coarse powder is placed in a planetary ball mill and ball-milled at a speed of 600 rpm for 4 to 6 hours to obtain tomato peel residue powder with an average particle size of 3 to 10 microns.

[0076] Example 2

[0077] This embodiment provides a polylactic acid nucleating agent with a plasticizing function, comprising dried tomato peel residue powder with an average particle size of 3 to 10 microns and a silane coupling agent, wherein the silane coupling agent may be KH550, KH560 or KH570, and the silane coupling agent used in this embodiment is KH550. The mass ratio of tomato peel residue to coupling agent KH550 is 5:1.

[0078] The preparation method of the polylactic acid nucleating agent of this embodiment comprises the following steps:

[0079] ① Put the tomato peel residue into a high-speed grinder for grinding to obtain tomato peel residue coarse powder;

[0080] ② Use a 20-mesh standard sieve to screen the coarse powder.

[0081] ③ Place the screened coarse powder and silane coupling agent in a planetary ball mill and perform ball milling at a speed of 600 rpm for 4 to 6 hours to obtain a tomato peel residue powder / silane coupling agent composite nucleating agent with an average particle size of 3 to 10 microns, such as Figure 1 shown.

[0082] Example 3

[0083] This embodiment provides a polylactic acid nucleating agent with a plasticizing function. The only difference between this embodiment and embodiment 2 is that the mass ratio of the tomato peel residue to the coupling agent KH550 is 3:1, and the rest is the same as embodiment 2.

[0084] Example 4

[0085] This embodiment provides a polylactic acid nucleating agent with a plasticizing function. The only difference between this embodiment and embodiment 2 is that the mass ratio of the tomato peel residue to the coupling agent KH550 is 9:1, and the rest is the same as embodiment 2.

[0086] Comparative Example 1

[0087] This comparative example provides a polylactic acid nucleating agent with a plasticizing function. The only difference between this comparative example and Example 2 is that wood powder is used instead of tomato peel residue powder, and the rest is the same as Example 2.

[0088] Comparative Example 2

[0089] This comparative example provides a polylactic acid nucleating agent with a plasticizing function. The difference between this comparative example and Example 2 is that steps ② and ③ are missing, and the coarse tomato peel powder obtained in step ① is directly used as the polylactic acid nucleating agent. The rest is the same as Example 2.

[0090] Example 5

[0091] This embodiment provides a polylactic acid composite material, comprising: polylactic acid and the nucleating agent prepared in Example 1, wherein the mass of the nucleating agent is 5% of the mass of the polylactic acid.

[0092] The preparation method of the polylactic acid composite material comprises the following steps:

[0093] ① Place the polylactic acid in an oven and dry it at 80°C for 6 hours to remove the moisture;

[0094] ② The nucleating agent prepared in Example 1 was uniformly mixed with polylactic acid, and then the mixture was melt-blended in a high-speed mixer.

[0095] The high-speed mixer can be a torque rheometer, or the mixture can be extruded and granulated by a parallel twin-screw, the temperature of the screw heating zone is 180°C, and the screw speed is 200 rpm. The method used for melt blending in this embodiment is to place the mixture in a torque rheometer, and perform melt blending at a temperature of 160°C and a speed of 40 rpm for 6 minutes.

[0096] The performance indicators of the composite material obtained in this example are shown in Table 1.

[0097] Example 6

[0098] This embodiment provides a polylactic acid composite material, comprising: polylactic acid and the nucleating agent prepared in Example 1, wherein the mass of the nucleating agent is 1% of the mass of the polylactic acid.

[0099] The performance indicators of the composite material obtained in this example are shown in Table 1.

[0100] Example 7

[0101] This embodiment provides a polylactic acid composite material, comprising: polylactic acid and the nucleating agent prepared in Example 1, wherein the mass of the nucleating agent is 15% of the mass of the polylactic acid.

[0102] The performance indicators of the composite material obtained in this example are shown in Table 1.

[0103] Example 8

[0104] This embodiment provides a polylactic acid composite material, comprising: polylactic acid and the nucleating agent prepared in Example 1, wherein the mass of the nucleating agent is 3% of the mass of the polylactic acid.

[0105] The performance indicators of the composite material obtained in this example are shown in Table 1.

[0106] Example 9

[0107] This embodiment provides a polylactic acid composite material, including: polylactic acid and the nucleating agent prepared in Example 2, and the rest is the same as Example 5.

[0108] The performance indicators of the composite material obtained in this example are shown in Table 1.

[0109] Example 10

[0110] This embodiment provides a polylactic acid composite material, including polylactic acid and the nucleating agent prepared in Example 3, and the rest is the same as in Example 5.

[0111] The performance indicators of the composite material obtained in this example are shown in Table 1.

[0112] Embodiment 11

[0113] This embodiment provides a polylactic acid composite material, including polylactic acid and the nucleating agent prepared in Example 4, and the rest is the same as Example 5.

[0114] The performance indicators of the composite material obtained in this example are shown in Table 1.

[0115] Comparative Example 3

[0116] This comparative example provides a polylactic acid composite material, including polylactic acid and a nucleating agent prepared in comparative example 1, and the rest is the same as in example 5.

[0117] The performance indicators of the composite material obtained in this comparative example are shown in Table 1.

[0118] Comparative Example 4

[0119] This comparative example provides a polylactic acid composite material, including polylactic acid and a nucleating agent prepared in comparative example 2, and the rest is the same as in example 5.

[0120] The performance indicators of the composite material obtained in this comparative example are shown in Table 1.

[0121] Table 1 shows the performance indicators of the composite materials obtained in Examples 5-11 of the present invention and Comparative Examples 3-4 and polylactic acid without adding a nucleating agent (the isothermal crystallization temperature is 96° C.).

[0122] Table 1

[0123]

[0124]

[0125] As shown in Table 1, the TP / PLLA composites prepared in Examples 5-8 are superior to polylactic acid without adding a nucleating agent in terms of crystallization rate, impact resistance and processing flowability, and the performance is the best when the mass of the nucleating agent is 5% of the mass of the polylactic acid. This shows that by controlling the particle size and content of tomato peel residue, after melt blending, the crystallization rate and mechanical properties of polylactic acid are effectively regulated. In addition, the thermal processing rheology of polylactic acid is significantly improved with the increase of the content of the nucleating agent, which increases the thermal processing stability of polylactic acid.

[0126] From Table 1, we further understand that the combined use of tomato peel residue and coupling agent can further increase the efficacy of the nucleating agent, thereby further improving the crystallization rate, impact resistance and processing flowability. In particular, Example 9 has the best effect, with the toughness of polylactic acid increased by 59.83%, while the tensile strength only decreased by 15.097%.

[0127] It can be seen from Comparative Example 3 that when wood powder is used instead of tomato peel powder to prepare the nucleating agent, the toughness and tensile strength of polylactic acid are greatly reduced.

[0128] It can be seen from Comparative Example 4 that when the tomato peel powder is used as the polylactic acid nucleating agent, the toughness and tensile strength of the polylactic acid are also greatly reduced.

[0129] By comparing Examples 9-11 with Comparative Examples 3-4, it can be seen that the nucleating agent prepared by the present invention not only increases the crystallization rate and crystallinity of the polymer, but also improves the rheological properties of the polymer.

[0130] The combined use of nucleating agents and plasticizers is a promising method to accelerate the crystallization kinetics of polylactic acid. Nucleating agents provide heterogeneous nucleation sites, while plasticizers increase the mobility of chains. However, in this study, it was found that tomato peel residues acted as both nucleating agents and plasticizers in the blend. It not only increased the crystallization rate and crystallinity of the polymer, but also improved the rheological properties of the polymer, which may be related to the ultrastructure and composition of the tomato peel residue powder prepared in the present invention. Under a scanning electron microscope, the tomato peel residue powder showed a densely stacked, relatively flat lamellar structure with sharp edges and corners. The only lamellar structure reported so far is two-dimensional materials such as graphene, which is obviously different from biomass fibers that are mostly rod-shaped and granular structures. The embodiments of the present application are described above in conjunction with the accompanying drawings, but the present application is not limited to the above-mentioned specific embodiments. The above-mentioned specific embodiments are only illustrative and not restrictive. Under the enlightenment of the present application, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present application and the claims, all of which belong to the protection of the present application.

Claims

1. A polylactic acid nucleating agent with plasticizing function, characterized in that: The invention comprises dried tomato peel residue powder and a silane coupling agent, wherein the silane coupling agent is KH550; The mass ratio of the tomato peel powder to the silane coupling agent is 5:1; The average particle size of the tomato peel residue powder is 3 to 10 microns.

2. The method for preparing the polylactic acid nucleating agent according to claim 1, characterized in that: The following steps are involved: ① Put the dried tomato peel residue into a high-speed grinder for grinding to obtain coarse tomato peel residue powder; ② Screening the coarse powder; ③ Place the screened coarse powder in a planetary ball mill and perform ball milling at a speed of 600 rpm for 4-6 hours to obtain tomato peel residue powder.

3. A polylactic acid composite material, characterized in that: include: Polylactic acid and the polylactic acid nucleating agent according to claim 1, wherein the mass of the polylactic acid nucleating agent is (1 to 15)% of the mass of the polylactic acid.

4. The polylactic acid composite material according to claim 3, characterized in that: The mass of the polylactic acid nucleating agent is (3-5)% of the mass of the polylactic acid.

5. The method for preparing the polylactic acid composite material according to claim 3 or 4, characterized in that: The following steps are involved: ① Place the polylactic acid in an oven and dry it at 80℃~90℃ for 6~8 hours to remove the moisture; ② Melt-blending the polylactic acid nucleating agent and polylactic acid in a high-speed mixer.